COMPARISON OF THE EFFECT OF ANTISEPTICS BASED ON DECAMETHOXINE, CHLORHEXIDINE BIGLUCONATE AND IODOFORM ON THE ADHESIVE POTENTIAL OF BACTERIA OF THE GENUS KOCURIA SPP - Loban, G.A.; Chumak, Yu.V.; Avetikov, D.S.; Ananieva, M.M.; Faustova, M.O.; Gavriliev, V.M.; Steblovskiy, D.V. (World of Medicine and Biology, 2022)
Antiseptics can block the adhesion of bacteria, thus facilitating the course of the purulent-inflammatory process. Therefore, we investigated the adhesive properties of clinical isolates of the genus Kocuria isolated from the oral cavity of patients with infectious-inflammatory post-extraction complications. Remedies based on decamethoxine, chlorhexidine bigluconate and iodoform were used as test antiseptics. The adhesive properties of clinical isolates under the action of remedies based on decamethoxine, chlorhexidine bigluconate and iodoform were determined by V.I. Brillis. The adhesion index values of microorganisms of clinical isolates of the genus Kocuria under the action of subbacteriostatic concentration of remedy based on decamethoxine were 1.6 times (p
Keywords: adhesion of microorganisms; pathogenic factors; antiseptics; clinical isolates; purulent-inflammatory process